PKWT (Perjanjian Kerja Waktu Tertentu) Pasca diberlakukannya Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja Menjadi Undang-Undang - Apriyansah, Apriyansah; Saputra, Adjie Bagus; Farhan, Luthfi; Yulaika, M. Rega (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The status of the employment relationship between workers/laborers and companies is an important aspect of employment because it determines the form of the employment agreement that binds both parties, whether it is a Fixed-Term Employment Agreement (PKWT) or an Indefinite-Term Employment Agreement (PKWTT). This difference in status has direct implications for workers' rights, especially when the employment relationship ends. The legal basis is regulated in Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, specifically Chapter IV. However, this study focuses on analyzing PKWT and the rights obtained by workers/laborers after the termination of their employment relationship with the company.